Blockchain technology : unlocking the value of 3Ts in the business world - Chauhan, Richa (Lecturer in business); Kaul, Vidhi (Apple Academic Press, 2025)
"This new volume, Blockchain Technology: Unlocking the Value of 3Ts in the Business World, explores the role of blockchain technology in promoting higher effectiveness in new business modeling in different industries, considering it as a key enabler of Industry 5.0 solutions that incorporate lean, transparent, traceable, and trustworthy mechanisms not only in logistics but also in other aspects of business processes. The volume looks at the incorporation of blockchain technology, often in conjunction with artificial intelligence, in diverse business sectors. Chapters look at the use of blockchain technology in the banking and finance sector; in the fashion industry; in the tourism, travel, and hospitality industries; in the national defense industry; for advertising and marketing; and, of course, in the logistics industry for enhancing green supply chains with blockchain technology, where it is being used to bring new levels of trust between trading partners and to promote end-to-end visibility. The volume looks at how blockchain technology is revolutionizing many industries by providing the means to automate processes, eliminate intermediaries, and provide real-time data access, thus reducing administrative burdens, minimizing errors, and improving overall efficiency."-- Provided by publisher.
Keywords: Blockchains (Databases) -- Industrial applications.; Blockchains (Databases) -- Economic aspects.; elektronické knihy; electronic books